Coding patterns used by ophthalmologists for hydroxychloroquine retinal toxicity - Chiu, Stephan; Shaw, Jeremy; Luong, Tiffany; Fong, Donald; Modjtahedi, Bobeck (Clinical ophthalmology (Auckland, N.Z.), 2018)
The aim of this study was to characterize International Classification of Diseases (ICD-9) coding patterns used by ophthalmologists in clinical practice for hydroxychloroquine (HCQ) retinal toxicity. This is a retrospective cohort study. Patients enrolled in the Kaiser Permanente Southern California health plan who were dispensed HCQ between 2001 and 2014 were included in this study. Patients' medical records were electronically searched for the following ICD-9 codes that can be used to characterize retinopathy or maculopathy: toxic maculopathy, non-exudative age-related macular degeneration (AMD), drusen (degenerative), and/or (other) background retinopathy. The charts of patients with these codes were then manually reviewed to determine which of these patients had been diagnosed by their ophthalmologists with HCQ retinopathy. ICD-9 codes used to indicate HCQ toxicity. A total of 23,362 patients were dispensed HCQ between 2001 and 2014. Of whom, 678 (2.9%) patients received at least one of the aforementioned ICD-9 codes with 53 having confirmed HCQ toxicity on chart review. Forty-three patients who were taking HCQ received a diagnosis code for toxic maculopathy, and of whom, 35 (81.4%) had HCQ toxicity. Of the patients with confirmed HCQ toxicity, 32.1% received a code other than toxic maculopathy to connote the presence of disease. Although toxic maculopathy is the most commonly used ICD-9 code to identify patients with HCQ toxicity, a significant number of patients with toxicity received other codes in their medical records. Additionally, almost one-fifth of the patients who were coded as having toxic maculopathy were ultimately not diagnosed with HCQ toxicity. This study underscores the often imprecise nature of ICD coding, especially in conditions without a specific associated code. The limitations of using coding information should also be considered when conducting research that utilizes electronic databases. Future investigations should determine how to improve database searches and methods to create more uniform coding standards among ophthalmologists, especially for rare conditions such as HCQ toxicity.